Method Comparison of Model Based Tomography and Grid Based Tomography to refine interval velocity - Yuninggar Dwi Nugroho; Sudarmaji S (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
The input data for pre stack time migration and pre stack depth migration is velocity model. The exact velocity model can provide maximum result in seismic section. The best seismic section can minimize possibility of errors during interpretation. Model based and grid based tomography are used to refine the interval velocity model. The interval velocity will be used as input in the pre stack depth migration. Initial interval velocity is obtained from RMS velocityusing Dix formula. This velocity will be refined by global depth tomography method. The global depth tomography method is divided into model based and grid based tomography. Velocity analysis is performed along the horizon (depth model). Residual depth move out is obtained from picking velocity. It is used as input in tomography method. The flat gather is obtained at tenth iteration. The interval velocity that is obtained from tenth iteration has the small errors. Tomography method can provide maximum result on velocity refinement. That is shown by the result that the pre stack depth migration is much better than using initial interval velocity. The pull up effect can be corrected by tomography method.